Burden and Historical Trend of Buruli Ulcer Prevalence in Selected Communities along the Offin River of Ghana. - Kobina Assan Ampah; Prince Asare; Daniel De-Graft Binnah; Samuel Maccaulley; William Opare; Katharina Röltgen; Gerd Pluschke; Dorothy Yeboah-Manu (Public Library of Science (PLoS), 2016)
Buruli ulcer (BU) is a neglected tropical skin disease caused by Mycobacterium ulcerans with more than two thirds of the global cases reported in West Africa. A nationwide active BU case search conducted in 1999 identified two health districts along the Offin River as two of the three most endemic districts in Ghana. Based on recent anecdotal accounts that transmission is unstable along the Offin River, we conducted from March to June 2013 an exhaustive household survey and active case search in 13 selected communities within a five-kilometer radius along the Offin River. The overall prevalence of BU was 2.3% among the surveyed population of 20,390 inhabitants and 477 of the total 480 cases detected (99.4%) were historical (healed) cases. By estimating the year of occurrence for each case per community and taking into account available passive surveillance records of health facilities and the District Health Directorate, we observed a general trend of continuous emergence of cases in communities located midstream the Offin River whereas downstream communities showed more sporadic patterns. We monitored the incidence of cases after the survey and recorded a cumulative incidence rate of 0.04% for the 13 communities over a 17-month active surveillance period from August 2013 to December 2014. Our data reveal an overall decline in BU incidence along the Offin River similar to the general decline in BU incidence in recent years reported by the World Health Organization for West Africa.